PENGARUH PENGAWASAN PEKERJAAN DAN KONFLIK KERJA TERHADAP STRESS PEGAWAI PADA CV. FAUTRA NUSANTARA BANDAR LAMPUNG - Ahirudin - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2013)
ACTHandling conflict in employees that are not appropriate and wise can impact on anuncomfortable work environment. It does not stop at the situation alone but can continue to be aburden on the employees themselves. The ability of employees in the face of conflict / stresscertainly not the same. It would be very dangerous for the employees who have the endurance toproblems / low pressure because they are in a state of uneasy atmosphere that mental pressure(stress).The study, conducted analytical research, this type of research is intending to make apresentation and to find the relationship and influence between variables - variables. From theresults of processing for proving hypotheses have been found answers to the hypothesis that jobcontrol significantly influence employee Stress in CV. Fautra archipelago. With the correlation (r)between variables X1 and Y is 36.6% of the variable (Y). While the value of r Square is at 0.133 or13.3 percent.Conflicts of work have a significant effect on CV Stress employees. Fautra archipelago. Withthe correlation (r) between the variables X2 and Y is equal to 0.414 This value gives the sense thatthe variable (X2), which is used in the model has a high correlation of 41.4% to variable (Y). Whilethe value of r is equal to 0.171 Square this means work can explain the variable Conflict of 17.1percent. Supervision of work and labor conflicts with the same significant effect on CV Stressemployees. Fautra archipelago. With the correlation (r) between the variables X1, X2 and Y is equalto 50.4% of the variable (Y). While the magnitude of R Square is equal to 0.254 means that thevariables X1, X2 able to explain by 25.4 percent to variable Y (Stress employees).